Effects of house prices on health: New evidence from Australia. (November 2017) - Atalay, Kadir; Edwards, Rebecca; Liu, Betty Y.J.
Abstract: Recent house price variation has strongly affected households' housing wealth and debt, yet the non-economic consequences of these changes in housing wealth are still poorly understood. Using a sample of 19, 000 individuals from the Household, Income and Labour Dynamics in Australia Survey (HILDA) for 2001–2015, we examine the relationship between house price fluctuations and individual health by exploiting large exogenous changes in house prices in Australia. We find that an increase in local house prices is associated with a positive effect on the physical health of outright owners and a negative effect on the physical and mental health of renters. Improvements in physical health for outright owners can be partially attributed to health-related investments and behaviours such as a reduction in weight, an increase in physical exercise and an increase in time allocated to home production. These findings support the presence of a health-wealth gradient through the wealth mechanism distinct from the effects of local area amenities and macroeconomic conditions. Our findings highlight some of the often-overlooked social impacts – both positive and negative – of fluctuations in the housing market. Highlights: We examine the impact of variation in house prices on physical and mental health. House price increases are associated with better physical health for outright owners. Renters who face rising house prices experience poorer mental and physical health. The effects can be partially attributed to changes in health-related behaviours.